Attitudes towards democracy and the market in Belarus: what has changed and why it matters. Issue 1 (4th March 2022) - Krawatzek, Félix; Langbein, Julia
ABSTRACT: For more than two decades a key pillar of regime stability in Belarus was legitimation through economic stability and security, prompting experts to speak of a "social contract" between the state and its citizens. The 2020 protests, however, convey significant dissatisfaction with the Lukashenka regime across a broad social and generational base. By comparing survey data from late 2020 with data from 2011 and 2018, we examine changing attitudes towards democracy and state involvement in economic affairs. We find a departure from paternalist values, implying an erosion of the value base for the previous social contract. Belarusian society has become more supportive of liberal political and economic values. This trend is particularly driven by the older generation and does not exclude Lukashenka's support base. Meanwhile, attitudes towards democracy and the market have implications for people's social and institutional trust, preference for democracy, and political participation.